The reality of female high school principals exercising the dimensions of creative leadership in the governorate of one of the theaters "case study" - Safhi, Ayshah Mahah (Journal of Educational and Psychological Sciences, 2023)
The research aims to identify the skills of the dimensions of creative leadership (sensitivity to problems, fluency, flexibility, originality) It is necessary to be available in the secondary school leaders in the governorate of Uhud Al-Masraha. And revealing the obstacles to practicing the dimensions of creative leadership (sensitivity to problems, fluency, flexibility, originality) among female secondary school leaders in Uhud Al-Masarha governorate from the point of view of the study sample members. It also aimed to develop a set of proposed mechanisms to overcome the obstacles to practicing creative leadership among female secondary school leaders in the governorate of Uhud Al Masarha. The researcher used the case study method as the best method for answering the questions of this research. She also used the interview tool to collect data in answering the paragraphs of the interview form that the researcher prepared. The research community was represented in all government secondary schools for girls in Uhud Al-Masharha governorate, which numbered (4) schools. The study sample included all school administration supervisors in the Education Office in the governorates of Al-Masharha and Al-Harith. Through the results of the theoretical framework and the interview, the researcher reached a set of recommendations and proposals, the most important of which are:- Developing the school’s organizational structure and structures in line with the appropriate organizational culture approach to the study community- Granting more powers to leaders in building organizational structures according to the needs of the vocational school, and in a way that helps leaders in administrative creativity- Supporting flexibility in rules and regulations to allow school leaders to develop and renew, and to allow them to make creative decisions
Keywords: Dimensions of Creative Leadership; practices; leadership; creativity; theater; secondary schools